2013
DOI: 10.1063/1.4807412
|View full text |Cite
|
Sign up to set email alerts
|

Origin of ferromagnetism in transition metal doped BaTiO3

Abstract: We have calculated the temperature, magnetic field, and ion doping dependence of the magnetic and electric properties in Fe-doped BaTiO 3 using a microscopic model and the Green's function technique. It is shown that the ferromagnetic and multiferroic properties observed at room temperature in Fe doped BaTiO 3 could be due to the super exchange interactions between Fe 3þ ions in different occupational sites associated with oxygen vacancies and to the exchange coupling of Fe ions with mixed valence, Fe 3þ and F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(36 citation statements)
references
References 37 publications
1
34
0
Order By: Relevance
“…The shifting of phase transition to the higher temperature is probably due to the ferromagnetism. However there are several studies which confirm the coexistence of ferroelectricity and ferromagnetism in BTF at low concentration of Fe and only ferromagnetism for high Fe contents [18][19][20]. The XRD results showed that the hexagonality of BTF samples grows up with the increase of doping concentration inducing ferromagnetism, as the hexagonal phase a well known as a ferromagnetic phase [19], which confirms the Tc shifting.…”
Section: Resultsmentioning
confidence: 49%
See 1 more Smart Citation
“…The shifting of phase transition to the higher temperature is probably due to the ferromagnetism. However there are several studies which confirm the coexistence of ferroelectricity and ferromagnetism in BTF at low concentration of Fe and only ferromagnetism for high Fe contents [18][19][20]. The XRD results showed that the hexagonality of BTF samples grows up with the increase of doping concentration inducing ferromagnetism, as the hexagonal phase a well known as a ferromagnetic phase [19], which confirms the Tc shifting.…”
Section: Resultsmentioning
confidence: 49%
“…Above 400 °C, a clear increase of dielectric constant was observed in the up and downhill for all the samples which indicates the existence of structural anomaly and it is confirmed at 0.6 of Fe content when εr′ reaches a maximum at 580 °C. [18].…”
Section: Resultsmentioning
confidence: 99%
“…Inducing ferromagnetism in semiconductor and insulators are rare due to the difficulty associated with the injection of spin into non-magnetic semiconducting system [3,4]. From the earlier reports, it was noted that various semiconducting materials such as ZnO, HfO 2 , TiO 2 , SnO 2 , and ATiO 3 (A = Sr, Ba) have been employed for DMS applications [5,10]. The origin of room temperature ferromagnetism in these kinds of wide gap semiconductors has been proposed due to defects in the host system [6,10].…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Another method is to add magnetic ions to a traditional ferroelectric material, such as BaTiO 3 , to induce a magnetic moment. [16][17][18] Although both approaches have been demonstrated conceptually, they share common challenges: (1) the order temperature of the developed materials is in most cases too low for practical applications; (2) the induced magnetization/ferroelectricity cannot be arbitrarily modulated by external electric/magnetic fields, because of weak coupling between the magnetization and ferroelectricity. One unique exception is BiFeO 3 (BFO), which exhibits a strong coupling between ferroelectricity and antiferromagnetism at room temperature (ferroelectric T C~8 30°C, antiferromagnetic T N~3 70°C).…”
Section: Introductionmentioning
confidence: 99%